Deformation and water/gas flow properties of claystone/bentonite mixtures - Chun-Liang Zhang (Journal of Rock Mechanics and Geotechnical Engineering, 2021)
As a potential engineered barrier material for disposal of radioactive waste in clay formations, claystone aggregate excavated from the Opalinus clay (OPA), its mixture with bentonite MX80 in a mass ratio of 7/3, and pure bentonite were extensively investigated with respect to the hydro-mechanical properties and performances. With these materials, a series of parallel experiments was performed under sequentially applied conditions of hydration with synthetic porewater of the clay formation, consolidation and water flow under increased stresses, and gas injection into the water-saturated and compacted materials under loading. Significant responses of the clay mixtures were observed. Main findings include: (1) the hydration and induced swelling of the mixtures are mainly dominated by bentonite content and dry density; (2) the consolidation decreases the porosity and water permeability exponentially by 2–3 orders of magnitude to low values of 10−18-10−20 m2 at stresses of 2–5 MPa, depending upon bentonite content; and (3) the gas penetration in the water-saturated and compacted bentonite is characterised by a cyclic pressure rising/dropping process limited in between the upper breakthrough and lower shut-off boundaries, whereas the compacted claystone and claystone/bentonite mixture allow for gas release at low and moderate pressures. The results are helpful for design of the engineered barriers for safe isolation of radioactive waste in repositories.